Pengelolaan Kompetensi Pendidik dalam Meningkatkan Kualitas Pembelajaran Tahfiz Al-Qur’an (Studi pada Primary Student One Islamic School Gunungsindur, Bogor) - Al Ghiffari, Rayhan Abizar; Sastradiharja, EE. Junaedi; Bahri Tanrere, Syamsul (Journal of Education and Islamic Studies, 2025)
ABSTRACT This study aims to analyze and describe the implementation of educator competency management, analyze and find the contribution of educator competency management to improving the quality of Tahfiz Al-Qur'an learning, and identify strategies to improve the quality of Tahfiz Al-Qur'an learning at Primary Student One Islamic School. The method used in this study is a survey method, with data collection techniques through interviews, observations and document studies. Data analysis uses a triangulation approach, namely data reduction, data presentation and conclusion drawing. The findings of this study are: First, the implementation of educator competency management at Primary Student One Islamic School is carried out through four stages, namely program planning, activity implementation, evaluation of success and follow-up or competency development. Second, educator competency management is proven to provide a significant contribution or contribution to improving the quality of Tahfiz Al-Qur'an learning at Primary Student One Islamic School. This is seen in the improvement of educator teaching quality, learning quality and student learning outcomes. Third, the strategy for improving the quality of Tahfiz Al-Qur'an learning is carried out through four strategies, including repeating memorization until it is truly memorized, understanding the meaning of the memorized verses, submitting memorization to educators and facilitating one type of mushaf.